2018
DOI: 10.1002/ajim.22831
|View full text |Cite
|
Sign up to set email alerts
|

The psychological distress and care needs of mesothelioma patients and asbestos‐exposed subjects: A systematic review of published studies

Abstract: This paper highlights the paucity of studies on the psychological distress and care needs of mesothelioma patients and asbestos-exposed subjects. It confirms that malignant mesothelioma is associated with the physical, emotional, and social functioning of patients, while also suggesting that the risk of developing asbestos-related diseases among asbestos-exposed subjects is associated with high levels of psychological distress, despair, and mental health difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Of the quantitative, Henson et al 37 was rated low, and Dooley et al 36 unclear. All three reviews 6,12,29 were rated unclear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the quantitative, Henson et al 37 was rated low, and Dooley et al 36 unclear. All three reviews 6,12,29 were rated unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 6,12,15,30 identified the first time‐period: pre‐diagnosis. For mesothelioma, there is an extra dimension around causality, and the ‘Damocles syndrome’ (retrospective awareness of personal risk from asbestos exposure was identified as a cause of anxiety and distress 6,12,15,30 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations